Agile manufacturing assessment model using multi-grade evaluation (Journal of Engineering, 2020)
In unpredicted industrial environment, being able to adapt quickly and effectively to the changing is key in gaining a competitive advantage in the global market. Agile manufacturing evolves new ways of running factories to react quickly and effectively to changing markets, driven by customized requirement. Agility in manufacturing can be successfully achieved via integration of information system, people, technologies, and business processes. This article presents the conceptual model of agility in three dimensions named: driving factor, enabling technologies and evaluation of agility in manufacturing system. The conceptual model was developed based on a review of the literature. Then, the paper demonstrates the agility evaluation by developing a multi-grade assessment model. This model can be used by decision maker to evaluate their current degree of agility. Lastly, the paper examined the conceptual model of evaluation in the State Company for Vegetable Oils Industry in Iraq. The calculation show that the State Company for Vegetable Oils Industry is very agile.